PENGARUH PERIKLANAN BERCITRA RELIGIUS (AGAMA ISLAM) DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PRODUK SUNSILK HIJAB REFRESH DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada Mahasiswi Universitas Diponegoro Semarang) - Edo Primadana; Budi Sudaryanto (Diponegoro Journal of Management, 2022)
Nowadays, competition between companies in marketing similar products is a special concern for marketers. Increasingly fierce competition is forcing managers to retry ways to win market share. One element that is starting to be widely used in advertising is using religious images (Islamic Religion) in advertising to attract and persuade potential consumers to buy the product. This study aims to analyze the religious image of the Sunsilk Hijab Refresh shampoo product in building buying interest and its influence on purchasing decisions. The population used in this study were active students at Diponegoro University, Semarang. The number of samples used in this study were 100 respondents. The method of data collection through a questionnaire. This research uses Structural Equation Modeling (SEM) analysis technique with AMOS analysis tool. The results of this study indicate that by including the context of Islam in the advertising of Sunsilk Hijab Refresh shampoo, it has a positive and significant effect on building consumer buying interest. After that, the buying interest that is built also has a positive and significant effect on a purchase decision.